Differentiation of Trafficking Pathways at Golgi Entry Core Compartments and Post-Golgi Subdomains - Ito, Yoko; Boutté, Yohann (Frontiers in Plant Science, 2020)
Eukaryotic cells have developed specialized membrane structures called organelles which compartmentalize cellular functions and chemical reactions. Recent improvements in microscopy and membrane compartment isolation techniques are now sophisticating our view. Emerging evidences support that there are distinct sub-populations or subdomains which are spatially and/or temporally segregated within one type of organelle, contributing to specify differential sorting of various cargos to distinct destinations of the cell. In plant cells, the Golgi apparatus represents a main trafficking hub in which entry occurs through a Golgi Entry Core Compartment (GECCO), that remains to be further characterized, and sorting of cargos is mediated through multiple transport pathways with different sets of regulator proteins at the post-Golgi compartment trans-Golgi network (TGN). Both GECCO and TGN are differentiated sub-populations as compared to the rest of Golgi, and moreover, further subdomain formation within TGN is suggested to play a key role for cargo sorting. In this review, we will summarize recent findings obtained on organelle subdomains, and their relationship with cargo entry at and exit from the Golgi apparatus.